2012
DOI: 10.1130/g33365.1
|View full text |Cite
|
Sign up to set email alerts
|

Mild Little Ice Age and unprecedented recent warmth in an 1800 year lake sediment record from Svalbard

Abstract: The Arctic region is subject to a great amplitude of climate variability and is currently undergoing large-scale changes due in part to anthropogenic global warming. Accurate projections of future change depend on anticipating the response of the Arctic climate system to forcing, and understanding how the response to human forcing will interact with natural climate variations. The Svalbard Archipelago occupies an important location for studying patterns and causes of Arctic climate variability; however, availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 43 publications
5
58
3
Order By: Relevance
“…In contrast to conditions inferred above, some other studies state a general warming trend (Bonnet et al, 2010;D'Andrea et al, 2012;Jernas et al, 2013;Majewski et al, 2009;Spielhagen et al, 2011;Werner et al, 2011) as well as a strengthened influx of AW during the last 2 millennia in the Svalbard area (Groot et al, 2014;Rasmussen et al, 2012;Sarnthein et al, 2003;Ślubowska et al, 2005). However, as the midHolocene is missing in the present record (see Sect.…”
Section: Late Holocene (∼ 18-04 Ka) -Aftermath Of the Neoglaciationcontrasting
confidence: 40%
“…In contrast to conditions inferred above, some other studies state a general warming trend (Bonnet et al, 2010;D'Andrea et al, 2012;Jernas et al, 2013;Majewski et al, 2009;Spielhagen et al, 2011;Werner et al, 2011) as well as a strengthened influx of AW during the last 2 millennia in the Svalbard area (Groot et al, 2014;Rasmussen et al, 2012;Sarnthein et al, 2003;Ślubowska et al, 2005). However, as the midHolocene is missing in the present record (see Sect.…”
Section: Late Holocene (∼ 18-04 Ka) -Aftermath Of the Neoglaciationcontrasting
confidence: 40%
“…The specific location of core JM09-KA11-GC within the influence of both AW (WSC) and ArW (Sørkapp Current, Bear Island Current) suggests that although sea ice cover was probably enhanced over the western Barents Sea during this climate deterioration, this local area was affected by a highly fluctuating sea ice boundary with strong seasonal gradients characterized by an early spring break up of the winter sea ice, and a strong spring/early summer stratification and AW dominance during summer (favoring E. huxleyi). The specific surface expression at this site is further confirmed by the overall similarities between our E / C proxy (JM09-KA11-GC) and reconstructed atmospheric temperatures from a lake record in western Svalbard (D'Andrea et al, 2012), an area influenced by similar hydrological features (e.g., sea ice, the Sørkapp Current and the WSC). D'Andrea et al (2012) identified a temperature increase starting at ∼ 1600 AD over western Svalbard as well as mild LIA summer conditions, which they explained by a strengthened WSC (NAC), a strengthening only inferred in the present study from our JM09-KA11-GC coccolith record.…”
Section: Reconciling the Observed Long-term Trends In Aw Flow And Dismentioning
confidence: 60%
“…Surface temperature variations also lead to temperature variations at depth but with different timescales than the penetration depth and temperatures certainly have not been constant in the past. It is known for example that there were periods warmer than the first decade of the 21st century (D'Andrea et al, 2012).…”
Section: Interpretation Of a Temperature Profile From Deep Drillingmentioning
confidence: 99%